Congruence of economic mobility beliefs and immigrants' self-esteem. Issue 2 (11th March 2019) - Guerrero, Laura; Turchick Hakak, Luciana
Abstract : Purpose: A dark side of global mobility is that many immigrants have negative work outcomes. Studies have analyzed the antecedents to poor work outcomes from the immigrants' point of view or from that of host country nationals. The purpose of this paper is to propose a relational model, which applies terror management theory to address how the economic mobility beliefs of immigrants and host country nationals interact and how these different combinations of beliefs affect the self-esteem of immigrants. Design/methodology/approach: This theoretical model considers the impact of the social interactions between immigrants and host country nationals when immigrants' mortality is salient. Findings: In hostile environments that make immigrants' mortality salient, lack of confirmation of immigrants' beliefs about economic mobility from host country nationals can lead to a decrease in immigrants' self-esteem and therefore to negative work outcomes. Practical implications: As the number of immigrants grows, so do concerns about their ability to contribute to the economy. Lack of confirmation of their beliefs in a context in which their mortality is salient, is likely to lead to lower self-esteem and perhaps other negative outcomes. Originality/value: This paper is the first, to the authors' knowledge, to use terror management theory to advance our understanding of the outcome of a lack of confirmation from host country nationals of immigrants' beliefs on economic mobility under conditions of mortality salience.